Female labour force participation in Arab countries: The role of identity - Tobias Caris; Bernd Hayo (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
We investigate why female labour market participation is low in the Arab region. Utilising Akerlof and Kranton's (2000) identity economics approach, we show in a simple gametheoretic framework that women socialised in a traditional family environment violate their identities by taking a job. In the empirical analysis, we study the respective impact of two determinants of identity in the Arab region, Islam and cultural tradition. Employing two waves of the World Values Survey, we find significant evidence that identity affects female labour market participation. Moreover, our estimates suggest that in the Arab region, Muslim women do not participate in the labour market less than non-Muslim women, whereas those with strong traditional identities have a 7 percentage point lower probability of entering the labour market.
Keywords: J16; J21; Z12; Z13; O53; 330; Female labour market participation; Arab region; Islam; Identity; Religion; Weibliche Arbeitskräfte; Erwerbstätigkeit; Persönlichkeitspsychologie; Soziale Werte; Islam; Arabische Staaten